The Tradition of Arisan Manakib Abdul Qadir Al-Jilani as a Basis for Strengthening Religious Moderation of Teenagers in Sraten Banyuwangi Village - Rahman, Fawait Syaiful (Prodi Sosiologi Agama, 2024)
Abdul Qadir al-Jilani's social gathering activities as a basis for strengthening religious moderation brought extraordinary changes to the attitudes, behavior and activities of teenagers. They are increasingly active in going to prayer rooms and mosques, as well as attracting the attention of parents to take part in these events. This research discusses the chronology, construction and implications of Abdul Qadir al-Jilani's social gathering tradition as a basis for strengthening moderation among teenagers in Sraten village. The research method used is qualitative with the type of field research. Data collection methods use interviews, documentation and observation, data analysis uses data reduction, data display and drawing conclusions. The research results showed that the tradition of Syaik Abdul Qadir al-Jilani's social gathering was motivated by the extreme behavior of Sraten village teenagers in the form of beatings of members of the community who had the status of the MD-affiliated al-Furqan mosque committee. Youth leaders and community leaders took the initiative to embrace teenagers following Manakib Syaikh Abdul Qadir al-Jilani which was packaged with a mobile social gathering. The menakib arisan tradition is a term for the institutionalization of Manakib Syaikh Abdul Qadir al-Jilani in society using the arisan system. The tradition of Shaikh Abdul Qadir al-Jilani's social gathering takes the form of a social gathering around reading and translating the manakib of Manakib Shaikh Abdul Qadir al-Jilani. This activity brought changes in the attitudes and behavior of teenagers from before and after following the Abdul Qadir al-Jilani social gathering tradition. Moderate behavioral changes based on anti-violence indicators so that the conflict over the al-Furqan mosque's place of worship is resolved through a lawsuit to the Surabaya PTUN.